Analysis of Road Network Development Strategies in South Sumatra Province - Ice Trisnawati; Sri Wiwoho Mudjanarko; Koespiadi Koespiadi (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
This study aims to establish a road development strategy in South Sumatra Province using a SWOT analysis approach. This research is located on the Road Network in South Sumatra Province, especially in Muara Enim Regency, while the time for this research is planned for 6 months, namely from July to December 2022. The population taken from this study are policymakers in the South Sumatra Province as the party in charge of developing the road network in Muara Enim Regency. In this study, the sampling technique used Non-probability Sampling with the Purposive Sampling method where the sampling technique has predetermined considerations for respondents with a total sample taken of 30 respondents. The results of the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) analysis place the road network development program in South Sumatra Province in quadrant 1. Position in quadrant 1 means that the program has opportunities and strengths. The strategy that must be taken in these conditions is to support an aggressive growth policy or growth-oriented strategy by taking advantage of existing opportunities and the organization’s internal strengths.